2020
DOI: 10.1002/ijop.12692
|View full text |Cite
|
Sign up to set email alerts
|

The role of child‐keyworker attachment in burnout among Saudi residential staff

Abstract: Research on the impact of the keyworker‐child relationship on residential staff is scarce. This longitudinal study investigated the potential moderating effects of child and keyworker attachment styles on the link between child behavioural problems and staff burnout and the moderating effects of child attachment style on the link between keyworker attachment style and keyworker burnout. Participants included 261 children and 59 residential child care workers, from 5 orphanages in Saudi Arabia. Five self‐report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…This is consistent with a study done by (Allday et al, 2020) that had a caregiver's age range of 30 -39. A study done by (Sochos & Aljasas, 2021) also found caregiver burnout among older age carers which is consistent with the findings in this study. Most of the carers were Malay.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with a study done by (Allday et al, 2020) that had a caregiver's age range of 30 -39. A study done by (Sochos & Aljasas, 2021) also found caregiver burnout among older age carers which is consistent with the findings in this study. Most of the carers were Malay.…”
Section: Discussionsupporting
confidence: 92%
“…Residential workers can become the targets of such behaviours (Berridge et al, 2011). Child behavioural problems are correlated and predictively associated with staff burnout (Sochos & Aljasas, 2021). Primary caregivers of children with a disruptive behavior disorders may be at particular risk for distress (Oruche et al, 2012) and conduct problems in particular were significant predictors of stress among carers of young people with autism spectrum disorders (Lecavalier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burnout is a significant concern among social workers internationally (Brown et al, 2019;Fong et al, 2022;Sochos & Aljasas, 2021); and child serving social workers have long been considered at particularly high risk (Anderson, 2000). Maslach and Leiter (2016) describe burnout as a three-dimensional syndrome resulting from prolonged workrelated exposure to interpersonal stressors.…”
Section: Introductionmentioning
confidence: 99%